A double-tracer radioisotope approach to assess simultaneous bioaccumulation of caesium in the olive flounder Paralichthys olivaceus. (October 2018) - Hansman, Roberta L.; Metian, Marc; Pouil, Simon; Oberhänsli, François; Teyssié, Jean-Louis; Swarzenski, Peter W.
Abstract: To better understand bioaccumulation of radiocaesium in the commercially important Japanese flatfish, Paralichthys olivaceus, the uptake and depuration kinetics of caesium via both seawater and food were assessed simultaneously using controlled aquaria. The pre-conditioned fish were exposed to radionuclides via the two different pathways (aqueous versus dietary) concurrently using two isotopes of caesium, 137 Cs and 134 Cs, respectively. Dissolved caesium uptake was linear and did not reach a steady state over the course of the 8-day exposure period. Consumption of 134 Cs-labelled food led to higher bioaccumulation rates of radioactive Cs than via seawater exposure of 137 Cs during uptake and following depuration, though the model-derived long-lived biological half-lives of both pathways was approximately 66 d. Further development of this method for assessing multiple radiocaesium bioaccumulation pathways simultaneously could lead to a promising new approach for studying Cs contamination in marine organisms. Highlights: A double-tracer method can simultaneously assess radiocesium biokinetics in fish. Food is the dominant pathway for radiocesium bioaccumulation in the olive flounder. Remaining cesium activity following depuration was low when compared to other fish.